ANALISIS KESIAPAN BELAJAR PADA SISWA KELAS VIII SEKOLAH MENENGAH PERTAMA NEGERI 1 SERASAN TIMUR - Jayatra, Rizky; Yuline, Yuline; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractLearning readiness is the initial condition that makes students ready to respond to a lesson given by the teacher in a certain way in any situation. The better students' learning readiness, the better the results they get in the learning activities they follow. Therefore researchers wanted to know more about the learning readiness of class VIII Serasan Timur Middle School 1. The general problem of this research was